(untitled) - Bunch, Bryan (New York, 1993)
n the heels of its highly successful predecessor The Timetables of Science, this expansive reference on technology takes readers from the invention of the wheel to the latest breakthroughs in technology.
Keywords: Technology,Công nghệ; History,Chronology,Tables,Lịch sử,Niên đại,Bản mục lục